1990
DOI: 10.1002/jnr.490270429
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor: A potential autocrine regulator of human glioma cell growth

Abstract: Basic fibroblast growth factor (bFGF) is a potent mitogen and angiogenic factor. bFGF is expressed by a variety of solid human tumors and has been implicated as an autocrine regulator of tumor growth. Different solid tumor lines including glioma, colon carcinoma and melanoma were examined for intracellular immunoreactive bFGF, high- and low-affinity bFGF receptors and mitogenic response to bFGF when grown in chemically defined medium. All tumor lines contained significant levels of bFGF. In addition, all tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…In addition, several endogenous angiogenesis inhibitors like the 16-KDa fragment of prolactin or like angiostatin can block FGF-induced phosphorylation of ERK isoforms p42/p44 in vitro, which further stresses the relevance of these pathways in the transduction of FGF intracellular signaling [18,19]. It has been also reported that FGF and their receptors are expressed at high rates in gliomas, and that their synthesis is upregulated during the transition from low-to-high-grade malignancy [15,16]. We therefore investigated whether this important signaling event in glioma cell proliferation was affected by dobesilate, as an assessment of whether FGF signaling was involved in the observed inhibitory activities of dobesilate [4], since dobesilate has been already reported to inhibit FGF activity in an angiogenesis model [3].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, several endogenous angiogenesis inhibitors like the 16-KDa fragment of prolactin or like angiostatin can block FGF-induced phosphorylation of ERK isoforms p42/p44 in vitro, which further stresses the relevance of these pathways in the transduction of FGF intracellular signaling [18,19]. It has been also reported that FGF and their receptors are expressed at high rates in gliomas, and that their synthesis is upregulated during the transition from low-to-high-grade malignancy [15,16]. We therefore investigated whether this important signaling event in glioma cell proliferation was affected by dobesilate, as an assessment of whether FGF signaling was involved in the observed inhibitory activities of dobesilate [4], since dobesilate has been already reported to inhibit FGF activity in an angiogenesis model [3].…”
Section: Discussionmentioning
confidence: 84%
“…Given the strict requirement of FGF for glioma growth [15,16], it seems reasonable to propose that the observed antiproliferative and proapoptotic activities of dobesilate in glioma cell cultures are also caused by an inhibition of FGF activity. If this is the case, alteration of the normal status of the FGF-triggered intracellular signaling system that drives cell division and survival should be expected.…”
mentioning
confidence: 99%
“…As a member of the FGF oncogene family which also includes aFGF, int-2, FGF-5, FGF-6, hst/K-FGF and KGF, bFGF has been suggested to play a crucial role in tumor progression. Strong evidence indicates that bFGF functions as an autocrine growth factor to stimulate cell growth and tumorigenesis of gliomas (Gross et al, 1990;Takahashi et al, 1990Takahashi et al, , 1991Takahashi et al, , 1992Stefanik et al, 1991;Ueba et al, 1994) and hepatocellular carcinoma (Lobb et al, 1986;Klagsbrun et al, 1986;Shimoyama et al, 1991). In human gliomas, the expression level of bFGF correlates with the degree of tumor malignancy (Takahashi et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…MAb ID11.16 was provided by one of the authors (JRD) and is a neutralizing antibody recognizing TGFI3, and TGF132 in Western blot analysis (23). MAb DG2 and DE6 were provided by one of the authors (JLG) and are neutralizing antibodies recognizing bFGF in Western blot analysis (24). All other antibodies were purchased as needed.…”
Section: Methodsmentioning
confidence: 99%
“…After drying in a vacuum oven (80°C for I hour), the membranes were incu- Synovial cell Iysates were also analyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Samples were first reduced in dithiothreitol and electrophoresed through 12.5% SDS-polyacrylamide gradient gels according to the method of Laemmli (26), and transferred electrophoretically for 30 minutes to nylon membranes (24). TGFf3 and bFGF bands were visualized by probing with MAb 1011.16 and DE-6, respectively , followed by peroxidaselabeled secondary antibod ies.…”
Section: Methodsmentioning
confidence: 99%